POLA KOMUNIKASI PIMPINAN DALAM MENINGKATKAN LOYALITAS KERJA KARYAWAN BP (BRAND PRESENTER) DI PT. BUDIMAN SUBRATA NIAGA PEKANBARU - Nur Azmi; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The research used a descriptive analysis with qualitative approach. Departing from the phenomenon that appears in the PT. Budiman Subrata Niaga Pekanbaru is the low comfort of employees while performing work that resulted in the lack of commitment and raises employees' desire to leave the company. The problem in this thesis is the communication patterns leader in improving employee loyalty. This study aims to determine how the processes and forms of communication patterns leader in increasing employee loyalty PT. Budiman Subrata Niaga Pekanbaru. The data in this study was obtained through in-depth interviews, observation, documentation, library research and internet searching. Data analysis techniques in this study is a model of data analysis techniques Miles and Hubberman by using the component data reduction, data presentation, and drawing conclusions and testing. Meanwhile, data validity checking techniques through extension of participation and triangulation. Results of the study showed that the pattern of leadership is communication made structural and familial patterns of communication in which the communication pattern has been running as expected. The communication process is done there feadback leaders, formal and informal communication and the message that was delivered in the form of informative and persuasive messages. Forms of communication patterns lead to tips leadership in strengthening leadership and employee relations, reward or prestige as well as providing knowledge and a sense of security for each employee. Keywords: organizational communication, communication patterns of leadership, loyalty work.